Assessment Of Different Experimental Vaccines Against Chlamydophila Abortus (Chlamydia Psittaci)In Rabits - Sanjeetha L (Department of Microbiology, College of Veterinary and Animal Sciences, 2003)
Two isolates of Chlamydia psittaci viz., M-430 and M-28, maintained in the Department of Microbiology, were used in the study. M-430 was used for the preparation of inactivated yolk sac and elementary body vaccines and M-28 was used for challenge experiment. These isolates were revived by inoculating to six to eight day-old chicken embryo through yolk sac route. Both isolates produced characteristic lesions in the embryo and yolk sac membrane. M-430 was also propagated in Mc Coy cell line for high yield of elementary bodies for vaccine preparation. Homogenous suspensions of the yolk sac and elementary body vaccines were inactivated with formalin to a final concentration of 0.4 per cent. Pure and safe preparations were used for vaccination trial. Immunogenic potential of the vaccines were tested in rabbits by giving two doses of each of the vaccines. The first dose was given at three months of age and second dose was given 14 days after the first. Three vaccinated and control rabbits were challenged with M-28 isolate on 28th day post vaccination and rest three on 70th day post vaccination. The clearance of elementary bodies from the tissues (lung, liver lymphnode and spleen) of vaccinated rabbits was an indication of the protection conferred by the vaccines. Better response was noticed with EB vaccine than yolk sac vaccine. The sera were collected from rabbits at regular intervals of 0, 7, 14, 21, 28, 42, 56 and 70 for passive haemagglutination and serum neutralization test. Both vaccines elicited good immune response. The greater humoral immune response of the rabbits that received EB vaccine suggests its slight superiority over the yolk sac vaccine. More evaluation and elaborated field trials on target species are required before advocating the vaccine for field use.